Faktor-Faktor dalam Financial Performance yang Mempengaruhi Tone Pengungkapan - Evelyn Shintania; Rachael Monica Salim; Saarce Elsye Hatane (Business Accounting Review, 2020)
Until now, the information in the company's annual report has not been utilized properly and optimally by external parties. Instead, all the important stakeholder’s decisions depend on the importance of understanding this information. This study develops the independent variables from previous research. The annual reports of several companies in Southeast Asia are used as the basis of data collection for this research. The purpose of this study is to prove that there is a significant relationship between financial performance and tone disclosure. This study use content analysis technique on the sentiment of qualitative annual report data to analyze tone disclosure. Then proceed with panel data regression analysis techniques to find a significant value between financial performance and tone disclosure. The samples are 92 company annual report data from five countries, namely: Indonesia, Philippines, Malaysia, Singapore and Thailand in the period of 2015-2019. The results of the Weighted Least Squared (WLS) show how financial performance and tone disclosure (positive or negative) are significantly related. This study finds other factors that also affect management disclosure in the company's annual report. The factors in financial performance which tested on this study are: company size, capital structure, liquidity, profitability and company’s risk.